Paclitaxel-related type I Kounis Syndrome in a very young patient with HER2-positive breast cancer and the role of genomics to disentangle a complex therapeutic scenario: a case report and narrative review - Javier Muñoz; Sabrina Nucera; Nuria Rubira Garcia; Isaac Cebrecos; Gabriela Oses; Sergi Ganau; Esther Sanfeliu; Pedro Jares; Mercedes Marín-Aguilera; Patricia Galván; Fara Brasó-Maristany; Olga Martínez-Sáez; et al. (Breast)
We present the first documented oncologic case of a type I Kounis syndrome (KS) following paclitaxel administration, in a very young patient with HER2-positive(+) early-stage breast cancer (BC). KS is a relatively rare acute coronary syndrome triggered by anaphylactic or hypersensitivity reactions, of which there is limited awareness among healthcare providers. It is subdivided in four subtypes depending on cardiac artery medical history. While no established management guidelines exist, its treatment requires addressing severe infusion reactions while ensuring proper myocardial perfusion. We hereby illustrate its successful acute management and report on how tumor genomics through the novel HER2DX assay helped re-defining the entire neo/adjuvant oncologic strategy. HER2DX integrates tumor size and nodal involvement with 27 genes’ expression data tracking four biological BC-related and immunologic signatures so to estimate a prognostic and a predictive score. This report demonstrates how clinical and genomic data can be effectively integrated to optimize therapeutic decisions in HER2+ BC, offering a model for personalized care also in atypical and complex cases.